Non-steroidal anti-inflammatory drugs induced acute kidney injury: incidence, clinical presentation, management and outcomes of patients at Tertiary Hospital based longitudinal study in Mymensingh, Bangladesh - Sattar, Shamima; Hasan, Mahmud Javed; Ray, Nitai Chandra; Quddus, ASM Ruhul (Community Based Medical Journal, 2018)
Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly prescribed in primary care for their analgesic and anti-inflammatory effects. Twelve percent of individuals currently report taking a NSAID daily. Renal injury caused by these agents can present in various forms, resulting from either acute or chronic use. Historically approximately five percent of patients initiated on NSAIDs experience a kidney-related adverse event. Drug-induced renal injury accounts for twenty percent of episodes of acute kidney injury (AKI). Patients requiring renal replacement therapy (RRT) have experienced an increased length of stay with associated healthcare costs per incident. The adverse effects of NSAIDs contribute to a significant economic burden, both to the patient and to the healthcare system.This study of NSAIDs induced AKI was carried out to highlight this issue. To find out the incidence, risk factors, diagnostic approach, clinical course, management and outcome of patients, this longitudinal study was carried out at Nephrology Department in Community Based Medical College Hospital Bangladesh from July 2015 to June 2016.Total 65 patients of NSAIDs induced AKI were included in this study. Any patient having pre existing renal pathology or chronic kidney disease was excluded from the study. Mean age of the patient was 36±7.12 yrs. Forty nine patients (74.38%) took NSAIDs at their own and 16 patients (24.61%) were prescribed by physician. Fifty six patients (86.15%) took NSAIDs because of musculoskeletal pain. Dehydration due to physical exertion (29.23%) gastroenteritis (16.92%) and nil per os (NPO) (6.15%)were the common predisposing factors. Common symptoms were swelling of the body (36.9%) headache (26.15%) fatigue (21.53%) and vomiting (13.84%) Oedema was the most common sign (36.9%) Blood urea and serum creatinine were raised in all patients. Treatment includes drug withdrawal (100%), fluid resuscitation (83.07%) fluid restriction (13.85%) short course of steroid (15.38%) and haemodialysis (10.76%) . Fifty one patients (78.46%) had complete recovery within two weeks of therapy whereas ten patients (15.38%) required more than two weeks to one month for complete recovery. Three patients (4.61%) developed chronic kidney disease (CKD). NSAIDs induced AKI carries a good prognosis with early diagnosis and proper management and it can be prevented by limiting the availability of over the counter drugs and creating awareness both in physicians and patients. These medications should be prescribed for the shortest duration, the lowest effective dose, and with careful surveillance to monitor nephrotoxicity precisely. NSAIDs should be used with special caution in elderly patients. CBMJ 2018 July: Vol. 07 No. 02 P: 09-16